Att synas eller inte synas? Islamic fashion i Stockholm - Rabo, Annika; Salim, Degla (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
This article describes, with Stockholm as an example, how Islamic fashion has become increasingly publicly visible in West Europe. We have made interviews focusing on aesthetic preferences and shopping habits and we have conducted wardrobe studies among young Muslim women. Some choose a strategy of conscious visibility and to be visibly Muslim in public space, thus confronting and challenging what they see as the patronizing gaze of mainstream Sweden. But the strategy of others is to be as invisible as possible in order not to draw attention to themselves and their headscarves. The women we have interviewed mainly shop in ordinary Swedish stores and creatively use various garments to combine into fashionable and Islamic look. In the text we also problematize our role as researchers since we have also, in a sense, helped produce Islamic fashion in Sweden by supporting an Islamic fashion catwalk.